THE USAGE OF BORON/BORON COMPOUNDS IN THE TEXTILE INDUSTRY AND ITS SITUATION IN TURKEY - (:unkn) unknown (CBU RESEARCH INST S R O, 2018)
Commonly found in the earth's crust, boron happens to be the 51st element of the periodic table and is not found in its elemental state in nature. It is known that there are about 230 different boron minerals in nature. Turkey has the largest boron reserves in the world. In addition to this, Turkey's boron minerals have the highest quality and production conditions that are more economical than other boron producing countries. For this reason, boron has great importance for Turkey and there is a significant demand for new areas of usage so that Turkey would be able to contribute to the national economy with these resources. The institute of BOREN (National Boron Research Institute) was established for this purpose in Turkey. This institute funds related projects for the extension of boron usage areas. One of the open sectors for innovation is textile technology. This study investigates the history of boron and its current situation in Turkey as well as the studies conducted regarding boron and its compounds especially in the textile field. Taking the available boron reserves in Turkey into consideration, the need for more research and development studies on boron as an environment-friendly element is clear for the textile industry.
Keywords: Boron Minerals; Boron Sources; Eco-friendly materials; Textile sector; BORON-COMPOUNDS; THERMAL-STABILITY; FLAME RETARDATION; BORIC-ACID; BORAX; WOOL